2004
DOI: 10.1038/sj.bjc.6601384
|View full text |Cite
|
Sign up to set email alerts
|

Infectious diseases in the first year of life, perinatal characteristics and childhood acute leukaemia

Abstract: The objective of the present study was to investigate the role of early common infections and perinatal characteristics in the aetiology of childhood common leukaemia. A case -control study was conducted from 1995 to 1998 in France, and included 473 incident cases of acute leukaemia (AL) (408 acute lymphoblastic leukaemia (ALL), 65 acute myeloid leukaemia (AML) age-, sex-and regionmatched with 567 population-based controls. Data on the medical history of the child and his/her environment were collected using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 32 publications
4
80
2
Order By: Relevance
“…They concluded that the risk of developing acute leukemia was decreased in children who were exposed to common infections in the first year of life (OR = 0.76; 95% CI: 0.67 to 0.87). [24,25] These findings are consistent with the findings of Perillat et al, Jourdan-Da et al, Dockerty et al, and Ma X et al [15][16][17][18][19]21,22] In New Zealand, Dockerty et al conducted a case-control study that included 121 children diagnosed with acute leukemia and 303 controls (with ages less than 14 years in both groups). They found that exposure to the influenza virus is a risk factor for developing leukemia; that is, a child infected with the influenza virus during the first year of life has a 7-fold risk of developing acute leukemia compared with children who had influenza, with an OR of 6.8 (95% CI: 1.8-25.7).…”
Section: Epidemiological Studiessupporting
confidence: 79%
See 3 more Smart Citations
“…They concluded that the risk of developing acute leukemia was decreased in children who were exposed to common infections in the first year of life (OR = 0.76; 95% CI: 0.67 to 0.87). [24,25] These findings are consistent with the findings of Perillat et al, Jourdan-Da et al, Dockerty et al, and Ma X et al [15][16][17][18][19]21,22] In New Zealand, Dockerty et al conducted a case-control study that included 121 children diagnosed with acute leukemia and 303 controls (with ages less than 14 years in both groups). They found that exposure to the influenza virus is a risk factor for developing leukemia; that is, a child infected with the influenza virus during the first year of life has a 7-fold risk of developing acute leukemia compared with children who had influenza, with an OR of 6.8 (95% CI: 1.8-25.7).…”
Section: Epidemiological Studiessupporting
confidence: 79%
“…These indicators are designated as "proxies" and include socioeconomic status, surgical history, allergic diseases, immunizations, attendance at daycare, breastfeeding, neonatal infections, and prenatal history, among others. [14][15][16][17][18][19][20][21][22][23][24][25] …”
Section: Measuring Exposure To Infection With Proxy Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13,24,44,59 Childhood infection Table 2 shows twenty-three studies that evaluated the association between childhood infection and leukemia. Among those that analyzed infections in the first two years of life, five reported reduced risk of ALL associated with infection in the skin, 44 ears, 48,81 or gastrointestinal tract, 25 and episodes of roseola and/or fever and rash.…”
Section: Maternal Infectionmentioning
confidence: 99%